Studi Pengolahan Limbah Fly Ash Batubara dalam Upaya Peningkatan Konsentrasi Silika Menggunakan Asam Sitrat - Chinara Abinawa; Alieftiyani Paramita Gobel (Yayasan Literasi Sains Indonesia, 2024)
The combustion of coal produces two types of waste, namely light ash (Fly Ash) and heavy ash (Bottom Ash). Fly ash is the waste generated by power plants, contributing to environmental pollution. According to data from the Ministry of Industry of the Republic of Indonesia in 2022, the current amount of fly ash and bottom ash in Indonesia continues to increase in line with the development and growth of the manufacturing industry as well as the increasing demand for electricity supplied by power plants. The combined fly ash and bottom ash generated from power plants alone in 2021 are estimated to reach 12 million tons, and it is projected to increase to 16.2 million tons by 2027. This poses a problem because the reused amount of fly ash and bottom ash is very small, necessitating the storage and/or landfilling of the remaining waste. The quantity of fly ash and bottom ash continues to grow without proper management, potentially contaminating the environment due to fine particles from coal combustion that become airborne. One way to utilize the silica contained in coal fly ash is through a hydrometallurgical extraction process. This process involves extracting metal compounds from ore using liquids such as acid. In the extraction process of silica from coal fly ash, pure citric acid is used as the extraction liquid. This process has several advantages compared to conventional processing methods, such as sintering or roasting, as it is more cost-effective, efficient, and environmentally friendly.